ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PER ANTARA SAHAM YANG TERCATAT DALAM INDEX SYARIAH DAN SAHAM BIASA (Studi pada Perusahaan Non Keuangan di Bursa Efek Indonesia 2006 -2008) - Ratnaningrum, Ratnaningrum; Susilowati, Heni (Benefit, 2010)
Price Earning ratio (PER) shows how much investors are willing to pay per rupiah of reported profit. Since a high PER shows that investor think that the firm has good growth opportunity, so factors determining of PER become very important means to investors in making investment decisions.This study examined the influence of current ratio, debt to equity ratio, return on equity, net profit margin, dividend payout ratio, and inventory turn over  on PER between stock listed in syariah index and common stock of non financial companies in the Indonesia  Stock Exchange (IDX). Samples used in this study consisted on 38 companies listed in IDX and 10 of them listed in Jakarta Islamic Index (JII). The data was analized using regression model and Chow test. The result showed  return on equity has negative influence on the join  PER. This coefficient was contrary with the expectation. This might due to the fact that the PER could increase because of  decreasing of the profit but not from the increasing of the stock price. Other result is a difference of the regression coefficient between stock listed in syariah index and common stock.